Fetal Membrane Cells for Treatment of Steroid‐Refractory Acute Graft‐Versus‐Host Disease123. (25th February 2013) - Ringdén, Olle; Erkers, Tom; Nava, Silvia; Uzunel, Mehmet; Iwarsson, Erik; Conrad, Réka; Westgren, Magnus; Mattsson, Jonas; Kaipe, Helen
Abstract The placenta protects the fetus from the mother's immune system. We have previously found that fetal membrane cells (FMCs) isolated from term placenta prevent alloreactivity in vitro. FMCs share many features with bone marrow‐derived mesenchymal stromal cells (MSCs), which we previously introduced to treat severe acute graft‐versus‐host disease (GVHD). Here, we tested FMCs for treatment of steroid‐refractory acute GVHD. After two passages in culture, approximately 109 FMCs were obtained from one single placenta, although not all cells from passage 0 and passage 1 were used for expansion. The FMCs were positive for CD29, CD44, CD73, CD90, CD105, and CD49d but were negative for hematopoietic, endothelial, and epithelial markers. Microsatellite polymorphism analysis showed that FMCs were of maternal origin. All FMCs used showed normal karyotype. Nine patients who had undergone hematopoietic stem cell transplantation (HSCT) and who had developed steroid‐refractory grade III–IV acute GVHD were given 0.9–2.8 × 106 FMCs per kg at 15 infusions. Median age was 57 years. There was no toxicity from infusion of FMCs in eight patients. One patient had seizures after infusion. Two of eight evaluable patients had a complete response and four had a partial response, giving an overall response rate of 75%. Two patients showed no response at all. Three patients are alive from 6 to 21 months after HSCT. One patient is well and two have chronic GVHD. Thus, FMCs may be successfully used for immune modulation and tissue repair. STEM CELLS2013;31:592–601